HGG-51. Uncovering therapeutic vulnerabilities in mismatch repair-deficient gliomas. (3rd June 2022) - Boynton, Adam; Pal, Sangita; Johnston, Ryan; Currimjee, Naomi; Qian, Kenin; Touat, Mehdi; Persky, Nicole; Goodale, Amy; Berstler, James; Miller, Lisa; Guletsky, Alex; Ligon, Keith L; et al.
Abstract: INTRODUCTION : We have observed that approximately 26% of recurrent gliomas acquire hypermutation following treatment with temozolomide (TMZ). Intriguingly, 91% of these tumors harbor mutations in mismatch repair (MMR) genes. Since MMR deficiency confers resistance to TMZ, strategies to target MMR-deficient gliomas stand to impact many patients. METHODS : We ablated the MMR genes MSH2, MSH6, MLH1, and PMS2 using an all-in-one sgRNA-CRISPR/Cas9 expression vector to generate isogenic MMR knockouts in patient-derived glioma cell lines. We characterized the gene expression profiles of these MMR-deficient glioma models and leveraged high-throughput drug screens and genome-scale CRISPR/Cas9 dropout screens to identify therapeutic vulnerabilities induced by loss of MMR. RESULTS : We show that loss of each major MMR gene confers resistance to TMZ. Gene set enrichment analysis of our MMR-deficient knockouts shows enrichment of several hallmark gene sets including DNA repair and G2M checkpoint signatures, and our genome-wide CRISPR dropout screen reveals that MMR-deficient cells are preferentially dependent on a number of genes involved in DNA repair and cell cycle, along with several other pathways. Lastly, the high-throughput drug repurposing (REPO) screen shows that loss of MMR confers differential dependencies to small molecule inhibitors. CONCLUSIONS : Using CRISPR/Cas9 to knock out individual MMR pathway members allows us to systematically study the response of MMR-deficient cells to alkylating agents in an isogenic context. Importantly, these isogenic models reveal that MMR-deficient glioma cells possess novel genetic dependencies and sensitivities to small molecules, which may inform future therapies for MMR-deficient tumors.